1987
DOI: 10.1051/rnd:19870508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and live weight on the sexual development of gilts and boars fed two planes of nutrition

Abstract: Summary. The Age had a significant influence on puberty attainment in gilts while live weight had nearly no effect. Percentages of cyclic gilts in the CTRL, SW and SA groups were 32, 79 and 20, respectively. Ovarian weight was mainly dependent on live weight in cyclic as well as in prepuberal gilts. In the latter animals, the weight and length of uterine horns and cervix were influenced by both age and live weight, whereas in cyclic gilts the only obvious effect was that of age on uterine horn weight. Season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
3
13
0
4
Order By: Relevance
“…At slaughter, the mean uterine weight was the lowest in immature gilts compared to pubertal ones. Similar observations on the uterine weight of immature and pubertal gilts have been done by Kauffold et al [27] and Prunier et al [15] after examination of the genital tract at slaughter.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…At slaughter, the mean uterine weight was the lowest in immature gilts compared to pubertal ones. Similar observations on the uterine weight of immature and pubertal gilts have been done by Kauffold et al [27] and Prunier et al [15] after examination of the genital tract at slaughter.…”
Section: Discussionsupporting
confidence: 84%
“…This period has been characterised by a decrease in LH and FSH secretions and an increase in ovarian secretions [11] which act on uterine development and the central nervous system [2,7,12,13]. The growth of the uterus has been observed during this period [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, a complete discrimination is not possible because as shown in the present study, the testes of one IC pig were heavier than those of four EMG pigs. Based on results of earlier studies, testes weight is highly correlated with BW in entire males (Prunier et al, 1987). Similarly, we report that testes of IC pigs are also heavier when slaughter weight increases.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, in the present study we have also observed a 59% decrease in 3b-HSD protein expression in heavyweight males (92 kg mean carcass weight) when compared with conventional-weight males (70 kg mean carcass weight). The onset of puberty is thought to be linked to the weight and the age of the pigs (Einarsson et al, 1979;Schinckel et al, 1984;Prunier et al, 1987). Generally, the pubertal development of boars occurs around the age of 5 to 6 months (Claus et al, 1994).…”
Section: Discussionmentioning
confidence: 99%